Influence of new coronavirus pandemic on behavior and awareness of young nurses and nursing students in Japan - Mitsuto Hasuike; Yoshiaki Hara; Hiroko-Miyuki Mori; Norio Ideguchi; Fumie Shirai; Yasuko Yoshimura; Ikumi Murakami; Hirohisa Kawahata; Motokuni Aoki; Toshio Ogihara (BMC, 2021)
Abstract Background Although mental health disorders of health care workers in the coronavirus disease 2019 (COVID-19) pandemic have been focused, little is known about the psychological impact on nurses and the influence on their behavior and awareness, such as professionalism and views on life and death, in Japan where there are fewer cases of infection and deaths than in other countries. Moreover, the influence of the pandemic on nursing students is still unclear. Methods An online questionnaire survey was conducted among nurses and nursing students. Feelings during the state of emergency (at the peak of the pandemic) in Japan, changes in behavior and awareness after the rise of COVID-19, and the associated factors influencing these changes were analyzed, comparing nurses with nursing students. Results Significantly increased scores of anxiety/fear (p < .005) and voluntary restraint (p < .005) and significantly decreased score of motivation (p < .005) were observed during the state of emergency in both nurses and students. Scores of experience of discrimination (p < .005) and consideration of premature retirement (p < .01) were significantly increased in nurses. Moreover, preventive behavior (p < .005), lifestyle (p < .005), anxiety about nursing (p < .005) and views on life and death (p < .005) significantly changed after the rise of COVID-19 in both nurses and students. Only nurses reported significant damage to their professionalism (p < .01). Anxiety/fear and/or voluntary restraint and/or decreased motivation during the state of emergency were major factors associated with these changes. Also, the type of hospital, experience of care of infected patients and sex affected some of the changes. Voluntary restraint (p = .008), increased preventive behavior (p = .021) and decreased motivation (p = .005) were more marked in nurses than in students, while change in views on life and death was greater in students than in nurses (p = .002). Conclusion The COVID-19 pandemic has had a psychological impact on nurses and nursing students, associated with changes in behavior and awareness even in Japan. Of note, the COVID-19 pandemic has affected nurses' professionalism and views on life and death. This study demonstrates the importance of having a coping strategy for anxiety and damaged professionalism in nurses, and education on life and death in nursing students.